Actualization of Social Status through Giving Traditional Objects in Traditional Ceremonies of the Toba Batak Community in the Lake Toba Region - Harisan Boni Firmando (Pena Cendekia Insani, 2021)
This paper aims to see the extent of the actualization of social status through the provision of traditional objects in the traditional ceremonies of the Toba Batak people. This study uses qualitative methods with data collection techniques of observation, interviews, document studies and focus group discussions. The results show that the life of the Toba Batak people in the Lake Toba area is regulated by the dalihan na tolu system, where this kinship system becomes the guideline for the community in social activities, especially in the implementation of various traditional ceremonies. There is a relationship between culture and social status, where traditional ceremonies become the arena of the Batak community. Toba to actualize his social status. Social status is actualized in various series of traditional ceremonies, ranging from traditional ceremonies before birth to traditional ceremonies after death, which include joy ceremonies and mourning ceremonies. The actualization of social status in various traditional ceremonies is carried out through efforts to provide rewards in the form of exchanging traditional objects between dalihan na tolu relatives. The giving of these traditional objects is a means of actualizing social status.